Fluorescence tumor imaging by i.v. administered indocyanine green in a mouse model of colitis‐associated colon cancer. Issue 5 (19th April 2018) - Nagahara, Rei; Onda, Nobuhiko; Yamashita, Susumu; Kojima, Miho; Inohana, Mari; Eguchi, Ayumi; Nakamura, Misato; Matsumoto, Shinya; Yoshida, Toshinori; Shibutani, Makoto
Abstract : Fluorescence tumor imaging using exogenous fluorescent tumor‐targeting agents has potential to improve early tumor detection. The fluorescent contrast agent indocyanine green (ICG) is used in medical diagnostics. The aim of the present study is to investigate the tumor imaging capability and the imaging mechanism of i.v. administered ICG in a mouse model of colitis‐associated colon cancer. To do this, an azoxymethane/dextran sodium sulfate‐induced colon cancer mouse model was used. Ex vivo imaging experiments were carried out 1 hour after i.v. injection of ICG. The ICG fluorescence was observed in the colon tumor tissues, with sufficient tumor to normal tissue ratio, correlating with tumor malignancy. In the tumor tissues, ICG fluorescence was localized in the vascular interstitial tissue. Immunofluorescence microscopy revealed that tumor cells formed tight junctions normally, suggesting an inability of tumor cellular uptake of ICG. In contrast, tumor tissues increased the CD31‐immunoreactive endothelial cell area, and accumulated stromal cells immunoreactive for COX‐2 and tumor cell population immunoreactive for inducible nitric oxide synthase. In vivo vascular permeability assay revealed that prostaglandin E2 promoted the endothelial cell permeability of ICG. In conclusion, our data indicated that fluorescence contrast‐enhanced imaging following i.v. administered ICG can be applied to the detection of colon tumors in a mouse colitis‐associated colon cancer model. The tumor tissue preference of ICG in the present model can be attributed to the enhanced vascular leakage of ICG involving inflammatory mediators, such as COX‐2 and inducible nitric oxide synthase, in conjunction with increased tumor vascularity. Abstract : The present study demonstrated that fluorescence contrast‐enhanced imaging following intravenously administered indocyanine green (ICG), a fluorescent contrast agent, can be applied to the detection of colon tumors in a mouse colitis‐associated colon cancer model. The tumor tissue preference of ICG in the present model can be attributed to the enhanced vascular leakage of ICG involving inflammatory mediators, such as COX‐2 and iNOS, in conjunction with increased tumor vascularity.